A Review for Characterization of Silica Fume and Its Effects on Concrete Properties - Panjehpour, Mohammad; Abang Ali, Abang Abdullah; Demirboga, Ramazan (International Journal of Sustainable Construction Engineering and Technology, 2011)
Mineral additions which are also known as mineral admixtures have been used in Portland cement for many years. There are two types of additions which are commonly mixed into the Portland clinker or blended directly with cement these days. They are crystalline, also known as hydraulically inactive additions and pozzolanic, which are hydraulically active additions. Silica fume is very reactive pozzolan, while it is used in concrete because of its fine particles, large surface area and high SiO2 content. Silica fume is much fined separated silica obtained as a by-product in industry. It is used as an admixture in the concrete mix and it has significant effects on the properties of the resulting material. Simultaneously, silica fume can be also utilized in production of refectory and porcelain, to increase intensity and durability. In addition, it can improve the overall performance of the material as filler used in coating resin, paint, rubber and other high molecular materials. This review paper discusses the effects of silica fume on the concrete properties such as strength, modulus, ductility, permeability, chemical attack resistance, corrosion, freeze-thaw durability, creep rate. Characterisation of silica fume as well as its physical and chemical properties will also be reviewed in this paper.